The occurrence of bacterial agents causing mastitis in dairy sheep and their resistance to antibiotics - Zigo, František; Lakticová, Katarína Veszelits; M, Mária Vargová (Jour Med Resh and Health Sci, 2020)
Introduction: The aim of this study was to monitor the occurrence of bacterial agents causing mastitis, forms of mastitis and antibiotic resistance in 300 ewes on a farm in Eastern Slovakia. Material and methods: During the milking season, were performed three complex investigations including clinical examination, California Mastitis Test and laboratory analysis of milk samples. The investigations and milk samples were taken in three phases; the beginning (April), the middle (June) and the end (September) of the milking season. Results: Of all the samples (806), 225 (28.0%) were positive for bacterial pathogens. The highest incidence of mastitis (33.3%) was recorded in September, while April (23.8%) and June (25.3%) had lower incidence. The samples from September showed the highest incidence of subclinical mastitis (20.1%), with 13.2% being an acute form of mastitis. Coagulase-negative staphylococci (CNS) were identified in 61.7% of the positive samples. Especially, S. chromogenes, S. epidermidis and S. schleiferi were most frequently isolated. Staphylococcus aureus was the causative agent in 20.0% of the positive samples and caused acute or subclinical mastitis in the affected ewes. The tested bacteria showed very high resistance to novobiocin (59.5%) and penicillin (51.4%) and high resistance to amoxycillin (35.1%). We found that 80% of Staphylococcus aureus bacteria tested for antibiotic resistance were resistant to novobiocin and 70% were resistant to penicillin. Of all tested CNS, 56.5% were resistant to novobiocin, 39.1% to penicillin, and 34.7% to amoxicillin. Conclusion: Proper isolation and identification of the causative organism play a significant role in the prevention and control of the intramammary infection. In our study, a combinations of Streptomycin, Ciprofloxacin and Tetracycline were the most effective antibiotics for the control of mastitis.